2018
DOI: 10.2147/jpr.s183096
|View full text |Cite
|
Sign up to set email alerts
|

Thermovision: a new diagnostic method for orofacial pain?

Abstract: BackgroundInfrared thermography can be used to obtain more complete information about a patient’s condition. The method can be used in various medical applications for monitoring acute and chronic orofacial pain syndrome. With this diagnostic method, thermal differences in the examined region are usually compared to the same reference region on the opposite side of the body.MethodsInfrared quantitative thermography is a non-invasive method for contactless monitoring of dynamic thermal fields on a surface, or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…No significant local temperature changes were found to be associated with a 0 or 1 VAS score. This result agrees with the literature which reports hyperthermal distribution in the presence of referred pain [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No significant local temperature changes were found to be associated with a 0 or 1 VAS score. This result agrees with the literature which reports hyperthermal distribution in the presence of referred pain [25].…”
Section: Discussionsupporting
confidence: 93%
“…The use of thermographic examination in the diagnosis of TMDs have been largely investigated in the literature [26][27][28][29], and several studies focused on myogenous pain [20,25] but only a few studies applied superimposition of ROI images [18,30]. A recent survey also assessed that facial nerve function is one of the possible biomedical applications of infrared thermography [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nosch et al reported that wind stimuli applied to the cornea at almost the same temperature as the cornea resulted in an increased corneal temperature when the stimulation was stronger [ 52 ]. Fricova et al reported that inflammation associated with orofacial pain increased in temperature in the facial region of the reported pain [ 53 ]. The pain sensation was thought to be related closely to blood flow and/or temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperspectral thermal imaging cameras can be mentioned as a very interesting direction of thermal imaging cameras development. Hyperspectral cameras recording the spectrum in a wide wave range can be used to identify very narrow spectral ranges for individuals, perhaps not only to assess the skin temperature on its surface but also by using appropriate algorithms for analysis and processing of temperature assessment images in 3D of inflamed tissues [21,66,67].…”
Section: Discussionmentioning
confidence: 99%